2016
DOI: 10.1111/tog.12263
|View full text |Cite
|
Sign up to set email alerts
|

Solid organ transplantation in pregnancy

Abstract: In the UK, there are approximately 50-60 pregnancies in women with solid organ transplants each year. Kidney transplants are the most common. Adverse maternal and fetal outcomes, including rates of preeclampsia, fetal growth restriction and preterm delivery, are higher in women with solid organ transplants than in the general obstetric population. Management of the solid organ transplant recipient in pregnancy includes pre-eclampsia prophylaxis and monitoring, screening for gestational diabetes and fetal growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…18 Decreased levels are particularly associated with the second trimester and monitoring should reflect this. 19 Doses require uptitration, aiming for pre-pregnancy targets, 20 with a 2-3 times increase often required. 15 Free tacrolimus levels (not routinely measured), are increased in pregnancy.…”
Section: Graft Dysfunctionmentioning
confidence: 99%
“…18 Decreased levels are particularly associated with the second trimester and monitoring should reflect this. 19 Doses require uptitration, aiming for pre-pregnancy targets, 20 with a 2-3 times increase often required. 15 Free tacrolimus levels (not routinely measured), are increased in pregnancy.…”
Section: Graft Dysfunctionmentioning
confidence: 99%
“…Tacrolimus and azathioprine have consistently been shown to be safe to take during pregnancy, without increased risk of congenital abnormality. 123,124 Whereas some studies have identified SOT recipients taking azathioprine and tacrolimus to be associated with preterm delivery and low birth weight, 125 these risks are similar across all transplant patients, irrespective of which immunosuppressant is being taken. As such, it is more likely to be related to underlying maternal condition, not as a direct consequence to immunosuppression.…”
Section: Immunosuppression and Rejectionmentioning
confidence: 99%
“…Tacrolimus and azathioprine have consistently been shown as safe to administer during pregnancy, with no increased risk of congenital abnormality 67 . However, potentially teratogenic immunosuppression, such as MMF, should be stopped a minimum of 6 weeks prior to embryo transfer, and replaced by a different agent, such as azathioprine.…”
Section: Fertility Considerationsmentioning
confidence: 99%
“…Tacrolimus and azathioprine have consistently been shown as safe to administer during pregnancy, with no increased risk of congenital abnormality. 67 However, potentially teratogenic immunosuppression, such as MMF, should be stopped a minimum of 6 weeks prior to embryo transfer, and replaced by a different agent, such as azathioprine. In cases where MMF has not been used, the potential time between implantation and embryo transfer can be reduced further to 3 months, potentially reducing further cumulative immunosuppression exposure.…”
Section: Fertility Considerationsmentioning
confidence: 99%